Analisis Kesalahan Berbahasa dalam Makalah Mahasiswa Program Studi Pendidikan Biologi Universitas Negeri Medan - Fazira, Hafizha; Fauziah, Fauziah; Barus, Dea Natalia; Lumbangaol, Sriyanti; Tansliova, Lili (Comit: Communication, Information and Technology Journal, 2024)
This research aims to determine and improve students' critical thinking skills in Indonesian language errors in writing papers for students in the biology education study program at Medan State University, which was carried out using a qualitative descriptive approach. Through qualitative descriptive research methods, researchers provide a real picture of what happened in the field, namely language errors in a biology education student's paper at Medan State University. The technique for collecting data used reading and note-taking techniques. In this research, the intralinguistic analysis method is used, namely an analysis method that compares linguistic elements with reference to the meaning of these language elements (linguistic properties). Includes errors ranging from the use of capital letters, italics and bold letters. The data source in this research is papers from biology education students at Medan State University. The results of this research show that the analysis of language errors contained in student papers is in the form of Indonesian spelling errors which include errors ranging from the use of capital letters, italics and bold letters. From the overall results of this research, 25 usage errors were found. Errors in the use of letters include 6 errors in the use of capital letters, 13 errors in the use of italics, and 6 errors in the use of bold letters. Errors in the use of Indonesian spelling occur because students are not careful, pay less attention and do not master the rules of good and correct writing so that there are still several errors that appear in writing papers.